Child unconsciousness in 'A Handful of Dates' by Saleh Tayib and 'The Veldt' by Brad Bury (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
A disappointment in parental behaviour towards children sometimes does not realized by parents. How parents raised their children is one of the reasons children unconsciously experience disappointment, reflected in the short story A Handful of Dates by Tayeb Salih and The Veldt by Ray Bradbury. This study shows that parental attitudes affect children's behaviour. This research uses the close reading method which includes: (1) analyzing the character of children and parents (2) identifying child’s unconsciousness (3) drawing conclusions about the effect of unconscious parental behaviour on children. This study uses psychoanalytic approach. Moreover, this study shows that parents' behaviour toward children’s unconsciousness can influence children's bad behaviour.